2019
DOI: 10.3390/metabo9110257
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Laboratory Comparison of Metabolite Measurements for Metabolomics Data Integration

Abstract: Background: One of the current problems in the field of metabolomics is the difficulty in integrating data collected using different equipment at different facilities, because many metabolomic methods have been developed independently and are unique to each laboratory. Methods: In this study, we examined whether different analytical methods among 12 different laboratories provided comparable relative quantification data for certain metabolites. Identical samples extracted from two cell lines (HT-29 and AsPc-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 44 publications
0
49
4
Order By: Relevance
“…× 50 mm, 4 μm particle size, Thermo Fisher Scientific) and a Dionex IonPac AS11-HC-4 μm column (2 mm i.d. × 250 mm, 4 μm particle size, Thermo Fisher Scientific) coupled with a Q Exactive, high-performance benchtop quadrupole Orbitrap high-resolution tandem mass spectrometer (Thermo Fisher Scientific) (IC/HRMS/MS) [ 29 ]. Cationic polar metabolites (e.g., amino acids, bases, and nucleosides) were analyzed via liquid chromatography (Nexera X2 UHPLC system, Shimadzu Co., Kyoto, Japan) with a Discovery HS F5 column (2.1 mm i.d.…”
Section: Skeletal Muscle Performancementioning
confidence: 99%
“…× 50 mm, 4 μm particle size, Thermo Fisher Scientific) and a Dionex IonPac AS11-HC-4 μm column (2 mm i.d. × 250 mm, 4 μm particle size, Thermo Fisher Scientific) coupled with a Q Exactive, high-performance benchtop quadrupole Orbitrap high-resolution tandem mass spectrometer (Thermo Fisher Scientific) (IC/HRMS/MS) [ 29 ]. Cationic polar metabolites (e.g., amino acids, bases, and nucleosides) were analyzed via liquid chromatography (Nexera X2 UHPLC system, Shimadzu Co., Kyoto, Japan) with a Discovery HS F5 column (2.1 mm i.d.…”
Section: Skeletal Muscle Performancementioning
confidence: 99%
“…compared the fold-change between two cell lines across 12 different laboratories. Their results suggested that relative values obtained from different analytical setups can be combined when the same sample was analyzed (Izumi et al 2019 ). Similarly, Triebl et al found that the use of shared reference materials beyond in-house quality controls (QCs) can even further improve the quality of data from shared studies and measurements (Triebl et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The CE-TOFMS that was used in the TMCS has the advantage of identifying ionic metabolites, which are major metabolites in cells. However, the reliability of metabolome data from CE–MS has been of great concern, and recently the data have been investigated from various aspects including migration timing (electrophoretic mobility) [ 32 ], and quantification of metabolites at the inter-laboratory [ 37 ] and cohort [ 2 ] levels. In this study, we described an approach to evaluate the reliability of automatically extracted peaks using the cohort study and proposed a pipeline to filter reliable peaks efficiently.…”
Section: Discussionmentioning
confidence: 99%